1997
DOI: 10.3109/00365529709007686
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose versus High-Dose Ursodeoxycholic Acid in Cystic Fibrosis-Related Cholestatic Liver Disease Results of a Randomized Study with 1-Year Follow-up

Abstract: VanBerge-Henegouwen GP. Low-dose versus high-dose ursodeoxycholic acid in cystic fibrosis-related cholestatic liver disease. Results of a randomized study with 1-year follow-up. Scand J Gastroenterol 1997;32:369-373.Background: Ursodeoxycholic acid (UDCA) is beneficial in cholestasis related to cystic fibrosis (CF). High-dose treatment has been recommended to compensate for bile salt malabsorption. We compared the results of low-dose (10 mg/kg/day) and high-dose (20 mg/kg/day) UDCA treatment on liver biochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…Prospective clinical trials of UDCA, at doses of 10 to 20 mg/kg/d for 6 to 12 months, have shown significant improvements in serum liver enzyme levels in pediatric patients with CF liver disease [44,45]. However, higher doses (20 mg/kg/d) may be necessary in the treatment of CF liver disease, compared with other forms of cholestasis [46,47]. In a 2-year uncontrolled study, UDCA therapy improved the liver histology, with less inflammation and bile duct proliferation, in seven of 10 patients with CFrelated liver disease [48].…”
Section: Treatmentmentioning
confidence: 98%
“…Prospective clinical trials of UDCA, at doses of 10 to 20 mg/kg/d for 6 to 12 months, have shown significant improvements in serum liver enzyme levels in pediatric patients with CF liver disease [44,45]. However, higher doses (20 mg/kg/d) may be necessary in the treatment of CF liver disease, compared with other forms of cholestasis [46,47]. In a 2-year uncontrolled study, UDCA therapy improved the liver histology, with less inflammation and bile duct proliferation, in seven of 10 patients with CFrelated liver disease [48].…”
Section: Treatmentmentioning
confidence: 98%
“…A higher dosage of UDCA (20 mg/kg/d) appears to be more effective than a lower dosage (10 mg/ kg/d) because the intestinal absorption of UDCA and, as a consequence, enrichment of bile with UDCA may be impaired when pancreatic insufficiency is present. 52 UDCA appears to be an effective and safe treatment in cholestatic liver disease of cystic fibrosis. However, its effect on survival has yet to be proven.…”
Section: Therapeutic Uses and Efficacymentioning
confidence: 99%
“…In a randomized trial, UDCA (15 mg/kg/d) improved clinical and biochemical parameters as well as liver histology [39]. A subsequent study showed that a dosage of 20 mg/kg/d provided greater improvement of liver tests than a lower dose [40]. Further studies are necessary to determine the effect of UDCA in disease progression and long-term outcomes in patients with CF-associated liver disease.…”
Section: Pediatric Cholestatic Liver Disease Cystic Fibrosismentioning
confidence: 96%